2009
DOI: 10.22323/2.08030203
|View full text |Cite
|
Sign up to set email alerts
|

Images of women in STEM fields

Abstract: This study investigated how eighth-grade students perceived images of women in STEM and non-STEM careers. Thirty-six images were posted on-line; we measured five characteristics of each image. Forty students participated in the study. We found that there were significant differences in attractiveness, creativity, and intelligence between STEM and non-STEM images. There were no significant differences for good at her job and organization. In addition, there were no significant differences among STEM and non-STE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…A variety of causes have contributed to failed recruitment efforts (Wang and Degol 2016), including social factors (Cho et al 2009;Lyon 2013;Thackeray 2016), institutional structures (Bottia et al 2015), poor advising (Lee 2008), and early education classroom environments (Han 2016). However, studies show that developing an identity linked to STEM from a young age (Bieri Buschor et al 2014;McCarthy and Berger 2008), having supportive families (Burge 2013;Lee 2016;Lyon 2013), access to quality advising (Byars-Winston 2014;Bystydzienski, Eisenhart, and Bruning 2015), and exposure to gender-inclusive video games (Bonner 2015;Borghetti 2014;Gilliam et al 2017) can all play a part in the choice to pursue a career in these disciplines before enrolling on college.…”
Section: Recruitmentmentioning
confidence: 99%
“…A variety of causes have contributed to failed recruitment efforts (Wang and Degol 2016), including social factors (Cho et al 2009;Lyon 2013;Thackeray 2016), institutional structures (Bottia et al 2015), poor advising (Lee 2008), and early education classroom environments (Han 2016). However, studies show that developing an identity linked to STEM from a young age (Bieri Buschor et al 2014;McCarthy and Berger 2008), having supportive families (Burge 2013;Lee 2016;Lyon 2013), access to quality advising (Byars-Winston 2014;Bystydzienski, Eisenhart, and Bruning 2015), and exposure to gender-inclusive video games (Bonner 2015;Borghetti 2014;Gilliam et al 2017) can all play a part in the choice to pursue a career in these disciplines before enrolling on college.…”
Section: Recruitmentmentioning
confidence: 99%
“…The clinical literature suggests that around puberty girls’ lose interest in exploring science, focusing on how they appear to others (e.g., Pipher, 1994), and their self-confidence and perceived competence (e.g., Harter, 1982) decline dramatically. Furthermore, research in STEM reported that programs targeting high school students, particularly girls, were too late (Cho, Goodman, Oppenheimer, Codling, & Robinson, 2009; Valian, 1998) and suggested the need for early exposure. Observations of elementary school girls who found they were interested in engineering in LEGO-Robotics camp (McIntyre & Jennings, 2009) lent support to studying students in late childhood.…”
Section: Finding Out What Children and Adolescents Think About Engineeringmentioning
confidence: 99%
“…Some studies concern visual representation in particular disciplines (Nerlich, 2008) or scientific topics (O'Neill and Smith, 2014). Portraits of scientists and science in popular media are also frequent subjects of analysis (Cho et al, 2009). Hentschell (2014) discusses the transfer of chromophotography, film recording and interactive simulation from the realm of science production to science popularization, with changes in meaning and simplification.…”
Section: Introductionmentioning
confidence: 99%